Pengaruh Minuman Kopi terhadap VO2max dan Pemulihan Denyut Nadi pasca Melakukan Treadmill (The Influence of a Coffee Drinks to VO2max and Pulse Recovery after Doing Treadmill) - Natasha Amelia; Cholis Abrori; M Ihwan Narwanto (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Coffee can be classified as a psicostimulant which cause person stay awake. Coffee contains any ingredients such as caffeine.Caffeine could improve the performance of athletes. VO2max is a highest ratio of oxygen consumed during intense physical activity. The purpose of this study was to determine the effect of caffeine consumption on VO2max and exercise recovery pulse. The study used experimental research with Randomized Clinical Trial (RCT) methods. There were 20 volunteers, who were divided into two groups. The control group was given a drink that contains no caffeine while the treatment group was given a drink containing caffeine. Then all volunteers were asked to perform Modified Bruce Treadmill Test procedure until exhaustion occurred then VO2max.The next 4 days were washing out period where the control and treatment groups swap the roles. The results showed the average value of VO2max in the treatment group was 30.69 ml/ kg/min higher than in the control group 25.98 ml/ kg/min, but the duration of pulse recovery in the treatment group was 127 minutes slower than the control group, 121 minutes, indicating to its effects as a stimulant. In conclusion, administration of caffeine increased VO2max, but delayed time of pulse recovery. Keywords: Modified Bruce Treadmill Test, pulse recovery, caffeine,VO2max